Development of interactive flipbook learning media on chemical bonding material - Aisyah Zahra Nurramadhani; Regina Purwita Sari; Nova Yunita Putri Olii; Muhammad Amir Masruhim; Agung Rahmadani (Universitas Muhammadiyah Malang, 2025)
Chemical bonding material is difficult for students, impacting low student learning outcomes. This is due to the limited learning media used in learning. This study aims to develop interactive flipbook learning media on chemical bonding materials. Research and Development (R&D) using the ADDIE development model is the research methodology employed. Interactive flipbook media design is made in HTML format, which brings up interactive elements such as hyperlinks to practice questions and displays learning videos. Based on the findings of the validation analysis, material experts, media experts, and learning practitioners deemed the interactive flipbook media to be in a very valid category. The practicality test of interactive flipbooks is obtained from the results of teacher and student practicality questionnaires supported by the results of teacher and student activity observations. The effectiveness test of interactive flipbooks can be seen from the N-Gain value and effect size supported by student response questionnaires. The results of the teacher's practicality questionnaire analysis were 96.67% with a very practical category, and students were 82.81% with a practical category, supported by teacher activity observations of 94.25%, and students with 93% with an excellent category. The results of the N-Gain analysis were 0.36 with a medium category. The effect size results were 1.26, which was a very strong effect, supported by the average student response questionnaire results of 85.12%. Thus, an interactive flipbook has been successfully developed, which is very practical and effective for learning chemical bonding materials.